Biofuel cell, electrode for biofuel cell, enzyme electrode, and electrode slurry for biofuel cell
By employing a polymer with specific structural units as an electrode binder in biofuel cells, the challenges of organic solvent use and inadequate enzyme binding are addressed, resulting in biofuel cells with enhanced output characteristics and reduced environmental and economic burdens.
Patent Information
- Application Number
- JP2024550554
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-30
- Filing Date
- 2024-03-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-03-27
AI Technical Summary
Existing biofuel cells face challenges with electrode binders using organic solvents like NMP, which damage equipment and have environmental impacts, and PVDF-based electrode slurries that inadequately bind conductive materials and lead to enzyme deactivation, resulting in insufficient output characteristics.
The use of a polymer (A) with specific structural units derived from nonionic and anionic ethylenically unsaturated monomers and a crosslinker with multiple ethylenically unsaturated bonds as an electrode binder, which provides effective binding and immobilization of enzymes while reducing environmental impact and production costs.
This solution enables the production of biofuel cells with improved output characteristics, low environmental impact, and reduced costs, suitable for screen printing and effective enzyme immobilization.
Smart Images

Figure 0007671926000007 
Figure 0007671926000008 
Figure 0007671926000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a biofuel cell, and an electrode, an enzyme electrode, and an electrode slurry used therein. [Background technology]
[0002] Research and development is underway on biofuel cells, which are next-generation fuel cells that use enzymes or microorganisms as electrode catalysts and generate electricity using biomass resources such as sugar, alcohol, and organic waste liquid as fuel (see, for example, Patent Documents 1 and 2). Biofuel cells that use enzymes generally generate electricity by oxidizing and decomposing fuel at the negative electrode (anode) using oxidizing enzymes to extract electrons, and by reducing oxygen at the positive electrode (cathode) using reductase enzymes to produce water.
[0003] One of the processes for easily and inexpensively manufacturing such biofuel cells is a method of patterning electrode materials by screen printing. Specifically, a common method is to prepare a slurry (electrode slurry) by dispersing a conductive material such as carbon powder in a binder (electrode binder) made by dissolving polyvinylidene fluoride (PVDF) in an organic solvent such as N-methylpyrrolidone (NMP), and then screen-print the slurry on a substrate and dry it to form an electrode pattern (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6994184 [Patent Document 2] JP 2021-140988 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, electrode binders using NMP, an organic solvent, have raised concerns about the damage they may cause to screen printing equipment, and the environmental burden posed by organic solvents has also been an issue. In addition, the adhesiveness of conductive materials in electrode slurries using PVDF was not necessarily sufficient. Furthermore, PVDF has high water repellency, and when using electrode slurries using PVDF, the enzymes were not immobilized sufficiently on the electrodes, and the enzymes were easily deactivated, which led to problems such as the inability to obtain a biofuel cell with sufficient output characteristics.
[0006] The present invention has been made to solve these problems, and aims to provide a biofuel cell that has a low environmental impact, is low cost, and exhibits good output characteristics, as well as an electrode for a biofuel cell, an enzyme electrode, and an electrode slurry for a biofuel cell that are suitable for use therein. [Means for solving the problem]
[0007] The present invention is based on the discovery that certain polymers are suitable as electrode binders when forming electrodes for biofuel cells by screen printing.
[0008] The present invention provides the following means. [1] A biofuel cell that generates electricity through an oxidation-reduction reaction catalyzed by an enzyme, the biofuel cell comprising an enzyme immobilized on at least one of an anode and a cathode, the anode comprising a conductive material (1) and an electrode binder (1), the cathode comprising a conductive material (2) and an electrode binder (2), at least one of the electrode binders (1) and (2) comprising a polymer (A), the polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinker (a3), the crosslinker (a3) having two or more ethylenically unsaturated bonds in one molecule. [2] A biofuel cell that generates electricity through an oxidation-reduction reaction catalyzed by an enzyme, wherein at least one of an anode and a cathode comprises a conductive material and an electrode binder, and an enzyme is immobilized thereon, the electrode binder comprises a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), and the crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule. [3] An electrode for a biofuel cell comprising a conductive material and an electrode binder, the electrode binder comprising a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), the crosslinking agent (a3) having two or more ethylenically unsaturated bonds in one molecule. [4][3] An enzyme electrode, in which an enzyme is immobilized on the electrode for a biofuel cell.
[0009] [5] An electrode slurry for a biofuel cell comprising an electrode binder, a conductive material and an aqueous medium, wherein the electrode binder comprises a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), and the crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule. [6] The electrode slurry for a biofuel cell according to [5], wherein a content of the electrode binder is 10 to 200 parts by mass per 100 parts by mass of the conductive material. Effect of the Invention
[0010] According to the present invention, it is possible to provide a biofuel cell, an electrode for a biofuel cell, and an enzyme electrode that have a low environmental impact, are low cost, and exhibit good output characteristics. Furthermore, according to the present invention, it is possible to provide an electrode slurry for a biofuel cell, which has a low environmental impact, is suitable for screen printing, and enables the production of a biofuel cell exhibiting good output characteristics. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a biofuel cell according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the configuration of a biofuel cell according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of an embodiment of the biofuel cell of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The definitions and meanings of the terms and expressions used in this specification are given below. The electrode for a biofuel cell is also simply called an "electrode" and refers to an electrode in a state before an enzyme is immobilized thereon, and is to be distinguished from an "enzyme electrode" on which an enzyme is immobilized. The expression "X to Y" (X and Y are numerical values) means a numerical range with X as the lower limit and Y as the upper limit. In a numerical range (e.g., a range of content, etc.), the lower limit and upper limit values described in stages may be combined independently. The lower limit and upper limit values of a numerical range may be replaced with numerical values described in the examples. The content of each structural unit constituting the polymer is determined based on the blending amount of the compound derived from each structural unit, which is the raw material for synthesizing the polymer. "(Meth)acrylic" is a general term for acrylic and methacrylic. Similarly, "(meth)acrylate" is a general term for acrylate and methacrylate, and "(meth)acryloyl" is a general term for acryloyl and methacryloyl. The glass transition temperature is the peak top temperature of the temperature derivative curve of differential scanning calorimetry (DSC), and is specifically measured by the method described in the Examples. The median particle size D50 is the 50% cumulative particle size on a volume basis determined from a particle size distribution curve measured by dynamic light scattering (DLS) for an aqueous dispersion sample.
[0013] [Biofuel Cell] A biofuel cell according to an embodiment of the present invention (hereinafter, referred to as the present embodiment) is a biofuel cell that generates power by an oxidation-reduction reaction catalyzed by an enzyme. An enzyme is immobilized on at least one of the anode and the cathode. The anode includes a conductive material (1) and an electrode binder (1), the cathode includes a conductive material (2) and an electrode binder (2), and at least one of the electrode binder (1) and the electrode binder (2) includes a polymer (A), the polymer (A) has a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), and the crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule. By forming an electrode using an electrode binder containing the polymer (A) having such a specific structure, a biofuel cell that has a low environmental impact, is low cost, and exhibits good output characteristics can be obtained.
[0014] The electrode on which the enzyme is immobilized may be either the anode or the cathode, or may be both. As the electrode on which an enzyme is immobilized, the enzyme electrode of the present embodiment described below is preferred. The biofuel cell of this embodiment generates power by an oxidation-reduction reaction catalyzed by an enzyme, and at least one of the anode and the cathode preferably contains a conductive material and an electrode binder, and has an enzyme immobilized thereon. The electrode binder contains a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), and the crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule. That is, only one of the anode and the cathode may be the enzyme electrode of this embodiment, or both may be the enzyme electrodes of this embodiment. When both the anode and the cathode are the enzyme electrodes of this embodiment, the substrates of the enzyme electrodes of the anode and the cathode, the electrode binders (1) and (2), and the conductive materials (1) and (2) may be the same or different. Examples of the substrate for the enzyme electrode include paper, cloth, resin film, metal materials, and inorganic materials such as ceramics. When the cathode is not the enzyme electrode of this embodiment, the cathode may be, for example, one to which an oxygen reduction catalyst containing a metal such as platinum is immobilized instead of an enzyme.
[0015] The fuel in the biofuel cell is not particularly limited as long as it is a substance whose oxidation is promoted by the enzyme. Examples of the fuel include sugar, alcohol, aldehyde, amino acid, amine, lactic acid, and uric acid. The fuel may be a substance that is hydrolyzed by the enzyme and then oxidized (for example, starch or cellulose that is hydrolyzed to glucose). The fuel may be one type alone or two or more types in combination. Among these, sugar is preferred from the viewpoint of output stability, ease of handling, and the like. The type of sugar is not particularly limited, and examples include monosaccharides, disaccharides, oligosaccharides, polysaccharides, and sugar alcohols. For example, glucose is preferably used.
[0016] The conductive material (1) and the electrode binder (1) constituting the anode, and the conductive material (2) and the electrode binder (2) constituting the cathode will be described later.
[0017] An example of the structure of a biofuel cell of this embodiment is shown diagrammatically in Figure 1. In the biofuel cell 10 shown in Figure 1, an anode 2 and a cathode 3 are formed on the same surface on one side of a substrate 1 containing a fuel. 2 is a schematic diagram showing another example of the structure of the biofuel cell of this embodiment. In the biofuel cell 20 shown in FIG. 2, an anode 2 is formed on one surface of a substrate 1 having a fuel, and a cathode 3 is formed on the other (opposite) surface. In this case, the substrate 1 also serves as a separator between the anode 2 and the cathode 3.
[0018] The biofuel cell of this embodiment can generate electricity by simply supplying gum syrup or the like as a fuel. In another embodiment, for example, by incorporating sugar as a fuel in the base material in advance, electricity can also be generated using water.
[0019] Other embodiments include, for example, a form in which the fuel cell is attached to the skin as shown in Fig. 3. In the example of Fig. 3, a biofuel cell 10 as shown in Fig. 1 is used, and a lead portion 4 is formed on each of the anode 2 and the cathode 3. The lead portion 4 is covered with a cover sheet 5, and the biofuel cell 10 is fixed to the skin 6 in such a manner that the substrate 1 is in contact with the skin 6. The biofuel cell 10 is fixed to the skin 6 using a cover sheet 5 It may be attached to skin 6 using an adhesive sheet, or it may be attached to skin 6 using a separate adhesive tape or the like.
[0020] 3, for example, an enzyme electrode with lactate oxidase immobilized thereon can be used as the anode 2, and an enzyme electrode with bilirubin oxidase immobilized thereon can be used as the cathode 3. In this case, sweat secreted from the skin 6 is absorbed into the base material 1, and electricity is generated using lactic acid contained in the sweat as fuel. Electricity can be taken out to the outside through the lead part 4.
[0021] As described above, the biofuel cell of the present embodiment can also be used as a biosensor when applied to a living body. For example, the biofuel cell can be attached to an adherend such as skin, clothing, or a diaper to detect the amount of substances in body fluids such as sweat, urine, blood, tears, or saliva supplied from the adherend as electric power, measure the fluctuations in the amount of electricity, and be useful for health management or measuring and managing the amount of exercise.
[0022] [Electrodes for biofuel cells] The electrode of this embodiment is an electrode for a biofuel cell comprising a conductive material and an electrode binder. The electrode binder comprises a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), and the crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule. By using an electrode produced using an electrode binder containing the polymer (A) having such a specific structure, a biofuel cell that has a low environmental impact, is low cost, and exhibits good output characteristics can be obtained.
[0023] The electrode of this embodiment is preferably used in at least one of the anode and cathode of the biofuel cell electrode. It is more preferable that the electrode of this embodiment is used in both the anode and the cathode, in which case the electrode binder contained in the anode and the electrode binder contained in the cathode may have the same composition or different compositions.
[0024] The electrode is preferably one in which at least the conductive material and the electrode binder are adhered to a substrate. Such an electrode can be produced by applying an electrode slurry containing the electrode binder, the conductive material, and an aqueous medium to a substrate and drying the applied slurry. Examples of the substrate include cloth, paper, and resin film. The substrate is preferably porous and exhibits good adhesion to the electrode binder in order to adhere the conductive material at a high density. From the viewpoint of consideration of the environmental load when disposing of the biofuel cell, for example, Japanese paper is preferably used. From the viewpoint of durability, for example, oil-resistant and water-resistant paper is preferably used. The electrode slurry may be applied to one side or both sides of the substrate.
[0025] Details of the electrode slurry, as well as the electrode binder, conductive material, and aqueous medium will be described later.
[0026] The method of applying the electrode slurry is not particularly limited. Examples of the application method include screen printing, reverse roll method, direct roll method, doctor blade method, etc. Among these, screen printing is preferred because it allows simple and efficient pattern formation. In the case of screen printing, for example, it is also possible to form an electrode pattern in which a lead portion and a plurality of electrodes are printed on a substrate using a conductive material such as carbon paste.
[0027] The electrode slurry applied to the substrate is dried to thoroughly remove the aqueous medium in the electrode slurry. The drying method is not particularly limited as long as the aqueous medium is thoroughly removed. Examples of the drying method include methods performed under conditions such as hot air, low-temperature air, reduced pressure or vacuum, and (far) infrared radiation. These drying conditions may be combined.
[0028] [Enzyme electrode] The enzyme electrode of the present embodiment is an electrode on which an enzyme is immobilized.
[0029] In the case of an enzyme electrode for the anode, an enzyme that promotes the oxidation of the fuel in the biofuel cell is used, and may be used in combination with an enzyme that facilitates the oxidation of the fuel by hydrolysis or the like. Examples of the enzyme used in the anode enzyme electrode include, for example, glucose oxidase or a combination of glucose oxidase and glucose dehydrogenase when the fuel is glucose; fructose oxidase or a combination of fructose dehydrogenase when the fuel is fructose; invertase or a combination of invertase and glucose dehydrogenase when the fuel is sucrose; amylase or a combination of amylase and glucose dehydrogenase when the fuel is starch; and lactate oxidase when the fuel is lactic acid.
[0030] In the case of an enzyme electrode for the cathode, an enzyme that promotes the reduction of oxygen is preferably used. Examples of the enzyme used in the cathode enzyme electrode include bilirubin oxidase and laccase.
[0031] The enzyme electrode can be produced, for example, by immobilizing an enzyme on an electrode. Alternatively, the enzyme electrode can be produced by coating a substrate with an enzyme-containing electrode slurry in which an enzyme is mixed with an electrode slurry, and then drying the electrode.
[0032] The method for immobilizing the enzyme on the electrode is not particularly limited, and can be performed, for example, by applying an enzyme solution to the electrode and drying it. The enzyme can be applied, for example, by dripping or impregnating the enzyme solution. The enzyme may be applied after applying a mediator.
[0033] The mediator is a redox compound that mediates electron transfer between the electrode and the enzyme, and is appropriately selected depending on the type of fuel and enzyme. The mediator is used by being supported on the electrode or dissolved in the electrolyte. When the mediator is supported on the electrodes, the mediator may be added to the electrode slurry and then applied to the electrodes, or the mediator may be applied after the electrodes are formed. The mediator may be supported on either the anode or the cathode, or on both.
[0034] Examples of the mediator include organic sulfur compounds such as thionine, thionine acetate, tetrathiafulvalene, and 2,2'-azinobis(3-ethylbenzothiazoline-6-ammonium sulfonate); quinone compounds such as hydroquinone, 1,2-naphthoquinone, and 1,4-naphthoquinone; ferrocene; ferricyanide; osmium complexes; and polymers modified with these compounds. One type of mediator may be used alone, or two or more types may be used in combination.
[0035] From the viewpoint of sufficiently promoting power generation, the enzyme immobilized on the electrode is preferably at a concentration of 0.001 U / cm 2 More preferably, 0.01 U / cm 2 More preferably, 0.1 U / cm 2 The amount of the enzyme immobilized on the electrode is preferably as large as possible, for example, 2000 U / cm 2 or less than 1000 U / cm 2 It may be less than 500 U / cm 2 It may be the following.
[0036] [Electrode binders for biofuel cells] The electrode binder of this embodiment contains a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), and the crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule. An electrode binder containing a polymer (A) having such a predetermined structure has a low environmental impact and has good dispersibility of conductive materials, and can give an electrode slurry suitable for screen printing. By using this electrode slurry, a biofuel cell that has a low environmental impact, is low cost, and exhibits good output characteristics can be produced.
[0037] Hereinafter, the electrode binder is a general term for the electrode binder (1) constituting the anode and the electrode binder (2) constituting the cathode, and the conductive material is a general term for the conductive material (1) constituting the anode and the conductive material (2) constituting the cathode.
[0038] The electrode binder of the present embodiment contains a polymer (A), and may further contain a water-soluble cellulose derivative (B) and other additives described below. In order to fully exert the effects of the present invention, the content of the polymer (A) in the electrode binder is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and may be 100% by mass.
[0039] (Polymer (A)) The polymer (A) has a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3). The polymer (A) may have other structural units in addition to the first structural unit, the second structural unit, and the third structural unit. In order to fully exert the effects of the present invention, the total of the first structural unit, the second structural unit, and the third structural unit is preferably 80 to 100 mass%, more preferably 85 mass% or more, even more preferably 90 mass% or more, and still more preferably 95 mass% or more, based on 100 mass% of all structural units constituting the polymer (A).
[0040] <First structural unit> The first structural unit constituting the polymer (A) is derived from a nonionic ethylenically unsaturated monomer (a1). In order to obtain a polymer (A) that satisfies the effects of the present invention, the content of the first structural unit in the total amount of the first structural unit, the second structural unit, and the third structural unit constituting the polymer (A) is preferably 60 to 98% by mass, more preferably 75% by mass or more, even more preferably 90% by mass or more, and more preferably 97% by mass or less, even more preferably 96% by mass or less.
[0041] The nonionic ethylenically unsaturated monomer (a1) from which the first structural unit is derived has one ethylenically unsaturated bond in one molecule and has neither an anionic functional group nor a cationic functional group. The nonionic ethylenically unsaturated monomer (a1) may be used alone or in combination of two or more kinds. As the nonionic ethylenically unsaturated monomer (a1), one or more selected from the group consisting of aromatic ethylenically unsaturated compounds, (meth)acrylic acid alkyl esters, and polar group-containing ethylenically unsaturated carboxylic acid esters are suitably used, and it is preferable to include any of these.
[0042] The aromatic ethylenically unsaturated compound contributes to good binding properties of the conductive material. Examples of aromatic ethylenically unsaturated compounds include styrene, tert-butylstyrene, α-methylstyrene, p-methylstyrene, 1,1-diphenylethylene, and benzyl (meth)acrylate. The aromatic ethylenically unsaturated compounds may be used alone or in combination of two or more. Among these, aromatic vinyl compounds are preferred, and styrene is more preferred.
[0043] The proportion of the aromatic ethylenically unsaturated compound in the nonionic ethylenically unsaturated monomer (a1) is preferably 25 to 70% by mass from the viewpoints of the binding property of the conductive material and the adhesion to the substrate, etc., more preferably 35% by mass or more, even more preferably 45% by mass or more, and more preferably 65% by mass or less, even more preferably 60% by mass or less.
[0044] The alkyl (meth)acrylate contributes to the ease of synthesis and durability of the polymer (A). Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate. The (meth)acrylic acid alkyl esters may be used alone or in combination of two or more. Among these, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and 2-ethylhexyl acrylate is more preferred. In terms of good flexibility of the electrode binder, the (meth)acrylic acid alkyl ester preferably has an alkyl group bonded to the (meth)acryloyloxy group having 2 to 9 carbon atoms, more preferably 4 to 9 carbon atoms, and even more preferably has an alkyl group having 4 to 9 carbon atoms bonded to the acryloyloxy group.
[0045] The proportion of the (meth)acrylic acid alkyl ester in the nonionic ethylenically unsaturated monomer (a1) is preferably 20 to 70% by mass from the viewpoints of the flexibility of the electrode binder, the binding property of the conductive material, the adhesion to the substrate, etc. It is more preferably 30% by mass or more, even more preferably 40% by mass or more, and more preferably 60% by mass or less, even more preferably 50% by mass or less.
[0046] The polar group-containing ethylenically unsaturated carboxylic acid ester contributes to good polymerizability during synthesis of the polymer (A) and mechanical stability of the electrode binder. Examples of the polar group of the polar group-containing ethylenically unsaturated carboxylic acid ester include a hydroxy group and a cyano group. Examples of polar group-containing ethylenically unsaturated carboxylic acid esters include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl acrylate, and (meth)acrylonitrile. The polar group-containing ethylenically unsaturated carboxylic acid esters may be used alone or in combination of two or more. Among these, 2-hydroxyethyl (meth)acrylate is preferred, and 2-hydroxyethyl methacrylate is more preferred.
[0047] The proportion of the polar group-containing ethylenically unsaturated carboxylic acid ester in the nonionic ethylenically unsaturated monomer (a1) is preferably 0.50 to 20% by mass from the viewpoints of good polymerizability during synthesis of the polymer (A), binding property of the conductive material and adhesion to the substrate, swelling resistance of the electrode binder during use of the battery, etc. It is more preferably 1.0% by mass or more, even more preferably 2.0% by mass or more, and more preferably 15% by mass or less, even more preferably 10% by mass or less.
[0048] <Second structural unit> The second structural unit constituting the polymer (A) is derived from an anionic ethylenically unsaturated monomer (a2). In order to obtain a polymer (A) that fully exhibits the effects of the present invention, the content of the second structural unit in the total amount of the first structural unit, the second structural unit, and the third structural unit constituting the polymer (A) is preferably 1.5 to 20 mass%, more preferably 3.0 mass% or more, even more preferably 4.5 mass% or more, and also more preferably 15 mass% or less, even more preferably 10 mass% or less.
[0049] The anionic ethylenically unsaturated monomer (a2) from which the second structural unit is derived has one ethylenically unsaturated bond in one molecule and has an anionic functional group. The anionic ethylenically unsaturated monomer (a2) may be used alone or in combination of two or more kinds. Examples of the anionic functional group include a carboxy group, a sulfo group, a phosphate group, etc. The anionic functional group may form a salt. As the anionic ethylenically unsaturated monomer (a2), one or more selected from the group consisting of ethylenically unsaturated carboxylic acids and salts thereof, and ethylenically unsaturated sulfonic acids and salts thereof are suitably used, and it is more preferable that all of these are included.
[0050] Examples of the ethylenically unsaturated carboxylic acid and its salt include unsaturated monocarboxylic acids such as (meth)acrylic acid and crotonic acid; unsaturated dicarboxylic acids such as maleic acid, fumaric acid and itaconic acid; half esters of unsaturated dicarboxylic acids, and their salts. The ethylenically unsaturated carboxylic acid and its salt may be used alone or in combination of two or more. Among these, (meth)acrylic acid and itaconic acid are preferred.
[0051] The proportion of the ethylenically unsaturated carboxylic acid and its salt in the anionic ethylenically unsaturated monomer (a2) is preferably 70 to 99% by mass from the viewpoints of good polymerizability during synthesis of the polymer (A), binding property of the conductive material, adhesion to the substrate, etc. It is more preferably 80% by mass or more, even more preferably 85% by mass or more, and more preferably 98% by mass or less, even more preferably 95% by mass or less.
[0052] Examples of ethylenically unsaturated sulfonic acids and their salts include parastyrenesulfonic acid and its salts. The ethylenically unsaturated sulfonic acids may be used alone or in combination of two or more. Among these, sodium parastyrenesulfonate is preferred.
[0053] The proportion of ethylenically unsaturated sulfonic acid and its salt in the anionic ethylenically unsaturated monomer (a2) is preferably 1.0 to 30% by mass from the viewpoints of good polymerizability during synthesis of the polymer (A), binding property of the conductive material, adhesion to the substrate, etc. It is more preferably 2.0% by mass or more, even more preferably 3.0% by mass or more, and more preferably 20% by mass or less, even more preferably 15% by mass or less.
[0054] <Third structural unit> The third structural unit constituting the polymer (A) is derived from the crosslinking agent (a3). The content of the third structural unit in the total amount of the first structural unit, the second structural unit, and the third structural unit constituting the polymer (A) is, from the viewpoint of the swelling resistance of the electrode binder during use of the battery, preferably 0.010 to 0.50 mass%, more preferably 0.020 mass% or more, even more preferably 0.030 mass% or more, and more preferably 0.30 mass% or less, even more preferably 0.10 mass% or less.
[0055] The crosslinking agent (a3) from which the third structural unit is derived has two or more ethylenically unsaturated bonds in one molecule. The crosslinking agent (a3) may be used alone or in combination of two or more kinds. The crosslinking agent (a3) can form a crosslinked structure by, for example, addition reaction of two or more ethylenically unsaturated bonds with ethylenically unsaturated bonds of other raw material compounds for synthesis of the polymer (A), i.e., the polymer (A) is a crosslinked polymer. Examples of the crosslinking agent (a3) include divinylbenzene, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, etc. Among these, divinylbenzene is preferred.
[0056] <Glass transition temperature> The glass transition temperature of the polymer (A) is preferably −30 to 100° C. from the viewpoints of the binding property of the conductive material, the adhesion to the substrate, good flexibility of the electrode binder, etc. It is more preferably −20° C. or higher, even more preferably −10° C. or higher, and more preferably 90° C. or lower, even more preferably 80° C. or lower.
[0057] <Particle size> The polymer (A) exists as dispersed particles in the electrode binder composition containing an aqueous dispersion medium. The suitable particle diameter of the dispersed particles varies depending on the form and particle size of the conductive material. In order to fully exert the effects of the present invention, the median diameter D50 of the particles in the aqueous dispersion is preferably 0.10 to 1.0 μm. It is more preferably 0.15 μm or more, even more preferably 0.20 μm or more, and more preferably 0.80 μm or less, even more preferably 0.50 μm or less.
[0058] <Synthesis method> The polymer (A) can be produced by polymerizing synthetic raw materials including a nonionic ethylenically unsaturated monomer (a1), an anionic ethylenically unsaturated monomer (a2), and a crosslinking agent (a3). The polymerization method is not particularly limited, and a suitable example is emulsion polymerization. Emulsion polymerization is carried out in an aqueous medium in the presence of a polymerization initiator, with the addition of a surfactant and other additives as necessary. The synthesis raw materials may be charged all at once or may be successively added by dropwise addition. The reaction is usually carried out at 30 to 90°C with stirring.
[0059] From the viewpoint of the stability of the polymer (A) in the reaction system, it is preferable to add a basic substance during or after the polymerization reaction, as necessary, to neutralize and adjust the pH. Preferred examples of the basic substance include ammonia, triethylamine, ethanolamine, morpholine, 2-amino-2-methyl-1-propanol, lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, etc. The basic substance may be used alone or in combination of two or more kinds.
[0060] The aqueous medium is water, a hydrophilic solvent, or a mixture thereof. Examples of the hydrophilic solvent include methanol, ethanol, isopropyl alcohol, N-methylpyrrolidone (NMP), and 1,3-butylene glycol. The aqueous medium is preferably water from the viewpoints of dispersion stability of the synthetic raw materials and the polymer, reduction of the environmental load, etc. A mixture of water and a hydrophilic solvent is also preferable within the range that does not impair the dispersion stability. The aqueous medium used in the synthesis of the polymer (A) may remain as it is after the synthesis as the aqueous medium constituting the electrode binder composition.
[0061] The amount of the aqueous medium used is appropriately adjusted depending on the dispersibility of the synthetic raw materials in the aqueous medium, the viscosity of the reaction system, etc. From the viewpoint of the moderate progress of the polymerization reaction, the amount of the aqueous medium used is preferably 50 to 300 parts by mass per 100 parts by mass of the total of the nonionic ethylenically unsaturated monomer (a1), the anionic ethylenically unsaturated monomer (a2), and the crosslinking agent (a3). More preferably, it is 80 parts by mass or more, even more preferably 100 parts by mass or more, and more preferably 250 parts by mass or less, even more preferably 200 parts by mass or less.
[0062] The polymerization initiator is not particularly limited, but a radical polymerization initiator can be used, for example, peroxides such as ammonium persulfate, potassium persulfate, hydrogen peroxide, and tert-butyl hydroperoxide. The polymerization initiator may be used alone or in combination of two or more. Redox polymerization may also be performed by using these polymerization initiators in combination with a reducing agent such as sodium bisulfite, Rongalite, and ascorbic acid.
[0063] From the viewpoint of the dispersion stability of the synthesis raw materials and the produced polymer (A) in the aqueous medium, the surfactant to be used is preferably at least one selected from the group consisting of nonionic surfactants and anionic surfactants. Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene polycyclic phenyl ethers, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, etc. The nonionic surfactants may be used alone or in combination of two or more kinds. Examples of the anionic surfactant include alkylbenzenesulfonates, alkyl sulfates, polyoxyethylene alkyl ether sulfates, and fatty acid salts.
[0064] As the anionic surfactant, a reactive surfactant having an ethylenically unsaturated bond is also preferably used. Examples of reactive surfactants include compounds represented by the following formulas (1) to (4). The reactive surfactants may be used alone or in combination of two or more. Among these, the compound represented by formula (4) is preferred, and sodium alkylaryl sulfosuccinate is more preferred.
[0065] [ka] In formula (1), R 1 is an alkyl group, and p is an integer of 10 to 40. 1 is preferably an alkyl group having 10 to 40 carbon atoms, and more preferably a linear alkyl group having 10 to 40 carbon atoms.
[0066] [ka] In formula (2), R 2 is an alkyl group, and q is an integer of 10 to 12. 2 is preferably an alkyl group having 10 to 40 carbon atoms, and more preferably a linear alkyl group having 10 to 40 carbon atoms.
[0067] [ka] In formula (3), R 3 is an alkyl group, M 1 is NH4 or Na. 3 is preferably an alkyl group having 10 to 40 carbon atoms, and more preferably a linear alkyl group having 10 to 40 carbon atoms.
[0068] [ka] In formula (4), R 4 is an alkyl group, M 2 is NH4 or Na. 4 is preferably an alkyl group having 10 to 40 carbon atoms, and more preferably a linear alkyl group having 10 to 40 carbon atoms.
[0069] The reactive surfactant not only exerts an emulsifying effect on the reaction system in emulsion polymerization, but also has copolymerizability with the nonionic ethylenically unsaturated monomer (a1), the anionic ethylenically unsaturated monomer (a2), and the crosslinking agent (a3), but is not considered to be a structural unit constituting the polymer (A) in this embodiment.
[0070] The amount of the surfactant added is preferably 0.050 to 1.2 parts by mass relative to 100 parts by mass of the total of the nonionic ethylenically unsaturated monomer (a1), the anionic ethylenically unsaturated monomer (a2), and the crosslinking agent (a3), from the viewpoints of stable progress of the polymerization reaction, dispersion stability of the synthetic raw materials and the produced polymer (A) in the aqueous medium, adhesion of the conductive material to the substrate, etc. More preferably, it is 0.10 parts by mass or more, even more preferably 0.15 parts by mass or more, and more preferably 1.0 part by mass or less, even more preferably 0.50 parts by mass or less.
[0071] Other additives include, for example, chain transfer agents such as thiol, thiol glycolic acid and its esters, 3-mercaptopropionic acid and its esters, and the like. The addition of other additives is optional, and they may be added within a range that allows the production of the polymer (A) that does not impair the effects of the present invention.
[0072] (Water-soluble cellulose derivatives (B)) The electrode binder of the present embodiment contains a polymer (A), and also preferably contains a water-soluble cellulose derivative (B). The water-soluble cellulose derivative (B) serves to facilitate dispersion of the conductive material in the electrode slurry.
[0073] Examples of the water-soluble cellulose derivative (B) include celluloses and their salts such as methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose; polyvinyl alcohol; and polyvinylpyrrolidone. Examples of the salts of celluloses include ammonium salts and alkali metal salts. The water-soluble cellulose derivative (B) may be used alone or in combination of two or more. Among these, carboxymethyl cellulose and its salts are preferred.
[0074] When the water-soluble cellulose derivative (B) is contained in the electrode binder, the content thereof is preferably 1 to 50% by mass from the viewpoint of obtaining good dispersibility of the conductive material without interfering with the function of the polymer (A), more preferably 5% by mass or more, even more preferably 10% by mass or more, and more preferably 40% by mass or less, even more preferably 30% by mass or less. The total content of the polymer (A) and the water-soluble cellulose derivative (B) in the electrode binder is preferably 80% by mass or more, more preferably 95% by mass or more, and may be 100% by mass.
[0075] [Electrode binder composition] The electrode binder composition contains the electrode binder of the present embodiment described above and an aqueous medium, and the polymer (A) is dispersed in the aqueous medium. The electrode binder composition can be produced by mixing the electrode binder and the aqueous medium. The mixing method is not particularly limited.
[0076] The aqueous medium in the electrode binder composition may be the same as the aqueous medium used in the synthesis method of the polymer (A) described above, and may be the same as or different from the aqueous medium used in the synthesis method of the polymer (A). The aqueous medium used in the synthesis of the polymer (A) may remain after the synthesis. The aqueous medium is preferably water from the viewpoints of dispersion stability of the electrode binder in the electrode binder composition, reduction of environmental load, etc. A mixture of water and a hydrophilic solvent is also preferable within a range that does not impair dispersion stability.
[0077] The content of polymer (A) in the electrode binder composition can be appropriately adjusted by optionally adding an aqueous medium during production of the electrode slurry. From the viewpoints of easy-to-handle viscosity, dispersion stability of polymer (A), and the like, the content is preferably 10 to 80 mass%, more preferably 15 mass% or more, even more preferably 20 mass% or more, and more preferably 70 mass% or less, even more preferably 60 mass% or less.
[0078] [Electrode slurry] The electrode slurry of this embodiment contains the electrode binder of this embodiment described above, a conductive material, and an aqueous medium. The electrode slurry can be produced by mixing an electrode binder, a conductive material, and an aqueous medium. The mixing method is not particularly limited, but in order to sufficiently and homogeneously disperse the conductive material, it is preferable to knead the mixture using, for example, a planetary centrifugal mixer.
[0079] The electrode slurry may contain other components in addition to the electrode binder, the conductive material, and the aqueous medium, as long as the effects of the present invention are not impaired. Examples of other components include surfactants from the viewpoint of dispersion stability, etc. In order to fully exert the effects of the present invention, the total content of the electrode binder, the conductive material, and the aqueous medium in the electrode slurry is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and may be 100% by mass. The aqueous medium in the electrode slurry is the same as that in the electrode binder composition described above.
[0080] Examples of the conductive material include carbon materials and metal materials. Examples of the carbon material include graphite, carbon black, and porous carbon. The conductive material may be used alone or in combination of two or more. Among these, from the viewpoints of ease of handling and enzyme immobilization, carbon materials are preferred, and porous carbon is more preferred. Examples of porous carbon include mesoporous carbon, specifically, mesoporous carbon produced by a template method such as Ketjen black, carbon nanotubes, graphene, MgO template carbon, etc. Among these, MgO template carbon is preferably used from the viewpoint of good immobilization of enzymes.
[0081] The content of the conductive material in the electrode slurry is preferably 40 to 85% by mass, more preferably 45% by mass or more, even more preferably 50% by mass or more, and more preferably 80% by mass or less, even more preferably 75% by mass or less, from the viewpoint of adhering a sufficient amount of the conductive material to the substrate.
[0082] The content of the electrode binder in the electrode slurry is preferably 10 to 200 parts by mass relative to 100 parts by mass of the conductive material, which is a sufficient amount for the conductive material to adhere to the substrate, more preferably 20 parts by mass or more, even more preferably 30 parts by mass or more, and more preferably 150 parts by mass or less, even more preferably 120 parts by mass or less, and even more preferably 60 parts by mass or less.
[0083] The total content of the electrode binder and the conductive material in the electrode slurry is preferably 40 to 80% by mass from the viewpoints of applicability of the electrode slurry to screen printing, reduction in the amount used, etc. It is more preferably 45% by mass or more, even more preferably 50% by mass or more, and more preferably 75% by mass or less, even more preferably 70% by mass or less. EXAMPLES
[0084] The present invention will be described in detail below with reference to examples. The present invention is not limited to the following examples, and various modifications are possible without departing from the gist of the present invention.
[0085] [Production of Polymer (A)] In the following synthesis examples, the methods for measuring various physical properties are as follows. <Glass transition temperature> Differential scanning calorimetry (DSC) was measured using a differential scanning calorimeter ("EXSTAR DSC7020", Hitachi High-Tech Science Corporation; heating rate 10°C / min, nitrogen gas atmosphere), and the peak top temperature of the DSC temperature differential curve was taken as the glass transition temperature. <Median diameter D50> The median diameter D50 (volume basis) was calculated from the particle size distribution curve measured by dynamic light scattering (DLS).
[0086] (Synthesis Example 1) A reaction vessel equipped with a cooling tube, a thermometer, a stirrer and a dropping funnel was charged with 60 parts by mass of ion-exchanged water and heated to 75°C. In this reaction vessel, a mixture containing a total of 100 parts by mass of nonionic ethylenically unsaturated monomer (a1), anionic ethylenically unsaturated monomer (a2), and crosslinking agent (a3), 0.20 parts by mass of Eleminol JS-20 (excluding solvent), 0.20 parts by mass of Hitenol 08E, and 80 parts by mass of ion-exchanged water was dropped over 3 hours and mixed with stirring. At the same time, a solution of 0.40 parts by mass of potassium persulfate dissolved in 10 parts by mass of ion-exchanged water was dropped over 3 hours, mixed with stirring and polymerized. Two hours after the completion of the dropwise addition, the reaction product was neutralized with 0.90 parts by mass of 25% by mass ammonia water to obtain a dispersion of polymer (A1) (polymer (A1) content: 40% by mass).
[0087] [Table 1]
[0088] Details of the surfactants in Table 1 are as follows: ELEMINOL JS-20: Sodium alkylaryl sulfosuccinate; "ELEMINOL (registered trademark) JS-20", manufactured by Sanyo Chemical Industries, Ltd.; anionic reactive surfactant; non-volatile content 38.5% by mass · Hitenol 08E: Polyoxyethylene oleyl cetyl ether ammonium sulfate; "Hitenol (registered trademark) 08E", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.; anionic surfactant
[0089] The polymer (A1) had a glass transition temperature of 15° C. and a median diameter D50 of 0.26 μm.
[0090] [Production of electrode slurry] The raw materials used in producing the electrode slurry are as follows: Porous carbon powder: "Knobel (registered trademark) MJ (3) 100-00" manufactured by Toyo Tanso Co., Ltd.; BET specific surface area 390 m 2 / g, total pore volume 0.91mL / g, micropore volume 0.15mL / g, mesopore diameter 75nm, bulk density 0.06g / mL Electrode binder composition (1): Dispersion of the polymer (A1) (electrode binder) produced in Synthesis Example 1 (non-volatile content: 40% by mass) Electrode binder composition (2): "Kureha KF Polymer L#9305", manufactured by Kureha Corporation; 5% by mass solution of PVDF ("Kureha KF Polymer L#9300": electrode binder) in NMP Electrode binder composition (3): Styrene-butadiene rubber (electrode binder) latex (non-volatile content 40% by mass) Electrode binder composition (4): PTFE (electrode binder) aqueous dispersion (non-volatile content 60% by mass)
[0091] The porous carbon powder, the electrode binder composition, and the additive medium were mixed in the compositions shown in Table 2 and kneaded with a planetary centrifugal mixer to produce electrode slurries 1 to 9, respectively. As shown in Table 2, the dispersibility of the porous carbon powder in the obtained electrode slurries was good (◯) for electrode slurries 1 to 8, and poor (×) for electrode slurry 9.
[0092] [Manufacturing biofuel cells] Biofuel cells were produced by the methods described below using electrode slurries 1 to 9. The cases where electrode slurries 1 to 6 were used are examples, and the cases where electrode slurries 7 to 9 were used are comparative examples.
[0093] Details of the materials and raw materials used in the construction of the biofuel cell are given below. Base material (washi paper): Water-repellent gasenshi paper; Izumo washi paper Base material (oil-resistant and water-resistant paper): "oil-resistant and water-resistant paper (3)", manufactured by Lintec Corporation Carbon paste: "JELCON CH-8", manufactured by Jujo Chemical Co., Ltd. AzBTS: 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid ammonium salt); manufactured by Tokyo Chemical Industry Co., Ltd. TTF: Tetrathiafulvalene GOD: Glucose oxidase; Fujifilm Wako Pure Chemical Industries, Ltd. Phosphate buffer: 1 mol / L phosphate buffer, pH 7.0 BOD: Bilirubin oxidase; Amano Enzyme Co., Ltd. · Triton X-100: Polyethylene glycol-tert-octylphenyl ether; "Triton (registered trademark) X-100"; manufactured by Roche Diagnostics; nonionic surfactant
[0094] A carbon paste was screen printed on the substrate and dried at 120°C for 20 minutes to form a lead. An electrode slurry containing 0.04g of AzBTS as a mediator was screen printed three times on the lead, and then dried at 45°C for 30 minutes to form 32 electrodes of 20mm x 5mm. The electrodes were then subjected to UV ozone cleaning for 15 minutes. The electrode pattern consisted of four anodes and four cathodes connected in series and four in parallel. A saturated methanol solution of TTF was dropped onto the part of the electrode corresponding to the anode as a mediator, and further, 20 μL of a solution (10 U / μL) in which GOD was dispersed in a phosphate buffer solution was dropped onto each anode. A solution (10 U / μL) in which BOD was dispersed in a phosphate buffer solution containing Triton X-100 at a concentration of 0.01% by mass was dropped onto the portion of the electrode corresponding to the cathode, at 20 μL per cathode. Thereafter, the electrode (patterned electrode) was dried under reduced pressure for 1 hour to prepare an enzyme electrode plate in which GOD was immobilized on the anode and BOD was immobilized on the cathode. The enzyme electrode plates using Japanese paper as a base material were prepared using electrode slurries 1, 7, and 8, and the enzyme electrode plates using oil-resistant and water-resistant paper were prepared using electrode slurries 1 to 6. Since electrode slurry 9 had poor dispersibility, a biofuel cell was not produced using it (Comparative Example 3).
[0095] In addition, a phosphate buffer solution containing glucose at a concentration of 0.1 mol / L was dropped onto another substrate (1 mL / cm 2 ) and dried at 100°C for 30 minutes to prepare a glucose-containing substrate. This glucose-containing substrate was placed on the enzyme electrode of the enzyme electrode plate to produce a biofuel cell.
[0096] [Output characteristic evaluation] The output of each biofuel cell produced by the above method was measured by linear sweep voltammetry (measurement conditions: two-electrode method, scanning potential open circuit voltage 0 V, scanning speed 1 mV / s) to determine the maximum output. The liquid during the measurement was supplied by dropping 1 mol / L phosphate buffer solution (pH 7.0). Table 2 shows the measured maximum output.
[0097] [Table 2]
[0098] As shown in Table 2, it was confirmed that the biofuel cell produced using electrode slurry 1 exhibited good output characteristics (Example 1). It can also be said that the biofuel cells produced using electrode slurries 2 to 6 exhibited good output characteristics (Examples 2 to 6). On the other hand, the biofuel cells produced using electrode slurries 7 and 8 had poor output characteristics (Comparative Examples 1 and 2). From the above, it can be said that the biofuel cell manufactured using the electrode slurry containing the aqueous electrode binder of this embodiment exhibits good output characteristics. [Explanation of symbols]
[0099] 1 Base material 2 Anode 3. Cathode 4 Lead section 5 Covering sheet 6 skin 10, 20 Biofuel cells
Claims
1. A biofuel cell that generates electricity through an oxidation-reduction reaction catalyzed by an enzyme, An enzyme is immobilized on at least one of the anode and the cathode, The anode comprises a conductive material (1) and an electrode binder (1); The cathode comprises a conductive material (2) and an electrode binder (2); At least one of the electrode binder (1) and the electrode binder (2) contains a polymer (A); The polymer (A) has a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3), The crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule, The polymer (A) is a polymer of a nonionic ethylenically unsaturated monomer (a1), an anionic ethylenically unsaturated monomer (a2), and a crosslinking agent (a3). Biofuel cell.
2. A biofuel cell that generates electricity through an oxidation-reduction reaction catalyzed by an enzyme, At least one of the anode and the cathode includes a conductive material and an electrode binder, and has an enzyme immobilized thereon; the electrode binder comprises a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3); The crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule, The polymer (A) is a polymer of a nonionic ethylenically unsaturated monomer (a1), an anionic ethylenically unsaturated monomer (a2), and a crosslinking agent (a3). Biofuel cell.
3. 1. An electrode for a biofuel cell comprising a conductive material and an electrode binder, the electrode binder comprises a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3); The crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule, The polymer (A) is a polymer of a nonionic ethylenically unsaturated monomer (a1), an anionic ethylenically unsaturated monomer (a2), and a crosslinking agent (a3). Electrodes for biofuel cells.
4. An enzyme electrode, comprising the electrode for a biofuel cell according to claim 3 on which an enzyme is immobilized.
5. An electrode slurry for a biofuel cell comprising an electrode binder, a conductive material, and an aqueous medium, the electrode binder comprises a polymer (A) having a first structural unit derived from a nonionic ethylenically unsaturated monomer (a1), a second structural unit derived from an anionic ethylenically unsaturated monomer (a2), and a third structural unit derived from a crosslinking agent (a3); The crosslinking agent (a3) has two or more ethylenically unsaturated bonds in one molecule, The polymer (A) is a polymer of a nonionic ethylenically unsaturated monomer (a1), an anionic ethylenically unsaturated monomer (a2), and a crosslinking agent (a3). Electrode slurry for biofuel cells.
6. The electrode slurry for biofuel cells according to claim 5, wherein the content of the electrode binder is 10 to 200 parts by mass per 100 parts by mass of the conductive material.
Citation Information
Patent Citations
Electrolyte material composition, membrane electrode jointing agent, electrolyte membrane with jointing layer, membrane-electrode assembly, and polymer electrolyte fuel cell
JP2010170837A
Aqueous catalyst paste composition for fuel batteries, and fuel battery
JP2015028932A
Composition for electrode formation used in microbial fuel cell, electrode and microbial fuel cell
JP2018170092A
Electrode for microbial fuel cell and microbial fuel cell
JP2021140988A
Toner
JP2022189436A